Clinicopathological and molecular characteristics of synchronous gastric adenocarcinoma and gastrointestinal stromal tumors. Issue 1 (December 2017) - Luo, Jun-Ming; Cao, Fa-Long; Meng, Chen; Lin, Li-Jun; Ma, Si-Qing; Peng, Shao-Hua; Gao, Hong-Ling; Javidiparsijani, Sara; Wang, Gui-Rong; Zhang, Meng-Lan; Xin, Jian-Guo; Wang, Yi-Chun; et al.
Abstract Synchronous gastric tumors that consist of both gastrointestinal stromal tumor (GIST) and adenocarcinoma are rare. We studied the clinicopathological and molecular characteristics of six cases containing both gastric adenocarcinoma and GIST. By means of immunohistochemical analysis, all GIST cells expressed CD117, CD34 and Dog1 in all six synchronous gastric adenocarcinomas with GIST, and in GIST alone. Sequencing analysis demonstrated that exon 11c-kit mutations were present in two of six synchronous tumors and four of five GISTs. One of the two exon 11c-kit mutations in synchronous adenocarcinomas with GISTs was an uncommon mutation of CTT > CCA at amino acid 576, and the other was a GTT deletion at amino acid 560. The mutation was a homozygous A > G mutation in exon 12 (amino acid 567) ofPDGFR-α . We concluded that the exon 11 mutations were the most important in both cases of synchronous gastric adenocarcinoma with GIST and GIST alone. The mutation rate was higher in GIST alone than in synchronous adenocarcinoma with GIST.